Microanalysis of the antiretroviral nevirapine in human hair from HIV-infected patients by liquid chromatography-tandem mass spectrometry - Huang, Yong; Yang, Qiyun; Yoon, Kwangchae; Lei, Yvonne; Shi, Robert; Gee, Winnie; Lin, Emil T.; Greenblatt, Ruth M.; Gandhi, Monica (Analytical and bioanalytical chemistry, 2011)
Sufficient drug exposure is crucial for maintaining durable responses to HIV treatments. However, monitoring drug exposure using single blood samples only provides short-term information and is highly subject to intra-individual pharmacokinetic variation. Drugs can accumulate in hair over a long period of time, so hair drug levels can provide drug exposure information over prolonged periods. We now report on a specific, sensitive, and reproducible liquid chromatography-tandem mass spectrometry method for measuring nevirapine (NVP), a widely used antiretroviral drug, levels in human hair using even a single short strand of hair. Hair samples are cut into small segments, and the drug is extracted in methanol/trifluoroacetic acid ( v/v , 9:1) shaken at 37 °C in a water bath overnight, followed by liquid–liquid extraction under alkaline conditions. The extracted samples are then separated on a BDS-C 18 column with a mobile phase composed of 50% acetonitrile containing 0.15% acetic acid and 4 mM ammonium acetate with an isocratic elution for a total run time of 3 min and detected by triple quadrupole electrospray multiple reaction mode at precursor/product ion at 267.0 > 225.9 m/z . Deuterated nevirapine-d5 was used as an internal standard. This method was validated from 0.25 to 100 ng/mg using 2 mg hair samples. The accuracies for spiked NVP hair control samples were 98–106% with coefficients of variation (CV) less than 10%. The CV for incurred hair control samples was less than 7%. The extraction efficiency for incurred control hair samples was estimated at more than 95% by repeated extractions. This method has been successfully applied to analyze more than 1,000 hair samples from participants in a large ongoing cohort study of HIV-infected participants. We also showed that NVP in human hair can easily be detected in a single short strand of hair. This method will allow us to identify drug non-adherence using even a single strand of hair. Figure Therapeutic drug monitoring using hair